LINKING ACCOUNTABILITY TO AUDIT DELAY: ROLE OF SIZE AND FINDINGS - Aulia, Rizkiya Faizatul; Periansya, Periansya; Fithri, Eka Jumarni (Kesatuan Press, 2025)
Audits of local government financial statements in Indonesia are conducted after submission to the supreme audit agency. Based on the 2021–2023 semester audit reports, although submissions were timely, audit delays increased, indicating the presence of other contributing factors. This study investigates the effect of local government size and audit findings on audit delays, with performance accountability as a mediating factor. A quantitative approach was applied using secondary data from 34 provinces during 2021–2023, analyzed through multiple linear regression and path analysis. The results show that local government size positively influences performance accountability, while audit findings negatively affect it. Audit findings are also identified as the only factor significantly influencing audit delays. However, performance accountability does not mediate the relationship between the independent variables and audit delays. Theoretically, this research enriches public sector literature on audit delay by examining the mediating role of performance accountability. Practically, the findings suggest that auditors and local governments can reduce audit delays by strengthening the management and resolution of audit findings.